Portable and Battery-Operated Isothermal Amplification Device Validation for Onsite Analysis of M. tuberculosis "DNA Hunter” - Agel, H. Esra (Indonesian Journal of Tropical and Infectious Disease, 2023)
Point-of-care (POC) devices play an important role in the protection of public health by providing rapid diagnosis of infectious diseases, patient management, and effective treatment. Fast, easy-to-interpret, environmentally resistant, and cost-effective POC tests that can be used practically in the field are gaining more and more importance every day. There is a need for portable devices that will enable rapid diagnosis kits to be used in the field for early diagnosis and treatment. The aim of this study is to evaluate the DNA hunter device that was developed in terms of providing the required temperature for M. tuberculosis (MTB) diagnosis of the loop-mediated isothermal amplification (LAMP) assay and visually evaluating the analysis results. The device in this study; handheld (total weight 430 g, outer dimensions 70 x 175 x 80 mm), the average operating time can reach a maximum temperature of 110 degrees in 2 minutes with a fully charged battery, and the processing time is about 90 minutes without being connected to electricity. It can display the pre-evaluation result on the screen with the full digital color sensor. The device can be adjusted to the desired reaction temperature and time. It also has software where sample registration numbers can be entered. DNA Hunter can be used for all analyses performed by the LAMP method and the results can be evaluated colorimetrically, thus it is well suited for POC testing.